The Quality Monitoring of Cistanches Herba (Cistanche deserticola Ma): A Value Chain Perspective - Jiang, Linlin; Zhou, Baochang; Wang, Xiaoqin; Bi, Yaqiong; Guo, Wenfang; Wang, Jianhua; Yao, Ruyu; Li, Minhui (Frontiers in Pharmacology, 2021)
Cistanches Herba was used as a medicine food homology, which was mainly produced in the Alxa region of northwest China. In recent years, it has been widely used in various food items. The increasing demand for Cistanches Herba has led to problems such as overexploitation and quality deterioration. The quality and safety of herbal medicines are critical and have been shown to be affected by the value chain (VC). Using the VC framework, the study is embedded in a larger study aiming to investigate the effects of different VCs types on the quality and stakeholders of Cistanches Herba. In this study, 90 Cistanches Herba samples were collected during fieldwork. An additional 40 samples were obtained from the herbal markets and medicine purchasing stations. Semi-structured interviews and key informant interviews were performed to collect data on stakeholders in major production areas. These samples were analyzed using high performance liquid chromatography (HPLC) coupled with the k-means clustering method; a targeted quality assessment strategy based on chemical analysis was adopted to understand the quality of Cistanches Herba. Based on market research, the collected samples were divided into different grades through k-means clustering analysis. Quality differences of Cistanches Herba in Alxa region were explored through DNA barcoding. Accordingly, 10 different types of VCs were determined in the production of Cistanches Herba. The results show that there is a close relationship between the quality of Cistanches Herba and stakeholder benefits. Vertical integration at different levels was found for independent farmer-based VCs, horizontal collaboration was found in the cooperative-based VCs. The vertical coordination has led to a more consistent traceability system and strict regulation of supply chains. At the same time, the Cistanches Herba were divided into three grades. Through DNA barcoding and chemical analysis, we found that the quality differences between Cistanches Herba in the Alxa area were not significant. It was found that geographical suitability and vertical integration could impact the quality and sustainable production of Cistanches Herba. At the same time, the well-developed VCs can provide products with reliable quality, and ensure adequate financial revenue for relevant stakeholders.